Cultivation of Islamic Education Values in Orphanage Children - Wellie Sulistijanti; Alfin Muslikhun; Muh Nasihin; Mukhlidin Mukhlidin (Yayasan Letiges Konsultan Sosial, 2024)
Instilling values ​​provides values, traits, and knowledge that become a reference for behaviour in everyday life. The values ​​of Islamic education are the values ​​contained in the Islamic religion's teachings, including aqidah and morals. This research aims to discover the processes, strategies and methods for instilling Islamic educational values ​​in foster children at the Muhammadiyah orphanage in Semarang City and the implications. The method used is qualitative with a field study type. Data collection was obtained by conducting observations, interviews and documentation with informants. The population in this study were all residents of the orphanage and the sample was 30 people. The data analysis uses content analysis. This research shows that instilling Islamic educational values ​​in foster children at the Muhammadiyah orphanage in Semarang City starts with the process, planning, implementation, and evaluation. The strategies implemented are routine and regular education, learning Islamic values, good time management, commitment and sincerity of caregivers and a pressure-free environment. The implications for instilling Islamic educational values ​​in Muhammadiyah orphanages include the values ​​of aqidah, worship and morals. This instilling of Islamic values ​​is carried out and implemented in daily behaviour, providing an excellent example after being given by caregivers to their foster children.